2013
DOI: 10.1089/jwh.2012.3707
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Mediterranean-Style and MyPyramid Diets on Weight Loss and Inflammatory Biomarkers in Postpartum Breastfeeding Women

Abstract: Background: Of postpartum women, 15%-20% retain ‡ 5 kg of their gestational weight gain, increasing risk for adult weight gain. Postpartum women are also in a persistent elevated inflammatory state. Both factors could increase the risk of obesity-related chronic disease. We hypothesized that breastfeeding women randomized to a Mediterranean-style (MED) diet for 4 months would demonstrate significantly greater reductions in body weight, body fat, and inflammation than women randomized to the U.S. Department of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 62 publications
1
32
0
Order By: Relevance
“…183 Four RCTs reported that a postpartum lifestyle intervention was effective in facilitating weight loss compared with a control group. [187][188][189][190] A recent meta-analysis of 11 studies with 769 women reported a significant mean −2.57 kg (−3.6 to −1.5) weight loss in the intervention group. In a subgroup analysis the most effective interventions were those with objective goals (use of heart rate monitors, pedometers, and exercise combined with intensive dietary intervention), which produced a −4.1 kg (−5.2 to −3.5) weight loss.…”
Section: Interventions To Mitigate the Effects Of Maternal Obesity Onmentioning
confidence: 99%
“…183 Four RCTs reported that a postpartum lifestyle intervention was effective in facilitating weight loss compared with a control group. [187][188][189][190] A recent meta-analysis of 11 studies with 769 women reported a significant mean −2.57 kg (−3.6 to −1.5) weight loss in the intervention group. In a subgroup analysis the most effective interventions were those with objective goals (use of heart rate monitors, pedometers, and exercise combined with intensive dietary intervention), which produced a −4.1 kg (−5.2 to −3.5) weight loss.…”
Section: Interventions To Mitigate the Effects Of Maternal Obesity Onmentioning
confidence: 99%
“…In addition, technology and social media afford opportunities for novel intervention techniques,andsomesuchinterventionshavebeen successful in small trials. Herring et al 20 conducted a small pilot randomized controlled trial of a technology-based intervention (skills training and self-monitoring 22 Many diets have been shown to be equally effective for weight loss in the general population; similarly, among postpartum patients, the low glycemic index diet, the Mediterranean diet, and MyPyramid diet were all successful for postpartum weight loss. 22,23 Importantly, dietary intervention has been shown to be cost-effective.…”
Section: Treatment Strategies For Postpartum Weight Loss: Counselingmentioning
confidence: 99%
“…Herring et al 20 conducted a small pilot randomized controlled trial of a technology-based intervention (skills training and self-monitoring 22 Many diets have been shown to be equally effective for weight loss in the general population; similarly, among postpartum patients, the low glycemic index diet, the Mediterranean diet, and MyPyramid diet were all successful for postpartum weight loss. 22,23 Importantly, dietary intervention has been shown to be cost-effective. 24 Hagberg and colleagues implemented a dietary behavior modification treatment among Swedish overweight and obese women and determined that costs per gained qualityadjusted life year (QALY) were 8643 to 9758 US dollars.…”
Section: Treatment Strategies For Postpartum Weight Loss: Counselingmentioning
confidence: 99%
“…An RCT has recently been carried out in a small number of overweight breastfeeding women [62] and both a Mediterranean diet and a MyPyramid diet were reported to support postpartum weight loss and reduce TNF-a and IL-6, biomarkers of inflammation, though these are not cytokines implicated in Th1/Th2 balance.…”
Section: Dietary Intervention In Infancy and Childhoodmentioning
confidence: 99%